Oral diseases in pregnant women. Literature review - González Chavarría, Guiselle (2018)
Pregnancy is a period in the life of the woman where changes occur both in her body and in the environment. Due to the hormonal changes that the woman undergoes during the pregnant state, her oral health is affected, triggering a series of alterations at the gingival level, which causes the presence of oral diseases. The objective of the bibliographic review is to analyze and update knowledge about different oral pathologies in pregnant women. The Medline, SciELO and Google Scholar databases were searched for case studies, clinical trials, meta-analyzes, systematic reviews and literature reviews dealing with the different oral pathologies that occur in pregnant women in the last 8 years. The “Free Full Text” filter was used as well, searching the keywords: pregnant women, oral diseases, oral health and their English counterparts. Seventy-two articles were obtained in the initial search, however, after excluding based on the criteria, 42 articles were selected given their relevant information. Most authors conclude that good oral hygiene habits and regular visits to the dentist can reduce adverse effects during pregnancy, although other researchers do not affirm the existence of a relationship between periodontal disease and adverse effects, but emphasize that periodontal treatment can be done during pregnancy to relieve the symptoms. Due to the changes suffered by women during the management, they require special and exclusive treatment, in addition to guiding her about oral care for both her and him after childbirth.